Surface porous graphite sheet
By adopting a surface porous graphite sheet, the sheet has a specific pore structure and can be directly compounded with the substrate without the need for adhesives. The problem of insufficient thermal resistance and heat resistance caused by adhesives is solved, and high viscosity is achieved A composite of contact and heat resistance.
Patent Information
- Application Number
- CN202080063387.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-12
- Filing Date
- 2020-08-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-08-06
AI Technical Summary
In the prior art, the adhesive may become a thermal resistance or a thermal resistance limitation in the composite of the substrate and graphite sheet, resulting in insufficient heat resistance of the composite.
A surface porous graphite sheet is used, which has a specific pore structure on the surface and inside, and can be directly compounded with the substrate without the use of an adhesive. The graphite sheet forms a structure of a porous layer and a graphite layer by depositing a resin layer on the resin sheet and heat treatment at high temperature.
The adhesive-free substrate and graphite sheet are compounded, the adhesion and heat resistance of the composite are improved, and the thermal resistance of the adhesive is avoided.
Smart Images

Figure CN114364526B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a surface porous graphite sheet. Background Art
[0002] There is known a technique for using a graphite sheet as a heat dissipation member by combining a substrate with a graphite sheet. This combination is usually accomplished by attaching the graphite sheet to the substrate using an adhesive.
[0003] For example, Patent Document 1 discloses a thermoelectric conversion device composed of an electrically insulating ceramic substrate, a graphite sheet with good thermal conductivity integrated with the ceramic substrate, and a thermoelectric conversion element supported by the ceramic substrate, and a heating element is provided on the graphite sheet side. In this document, the graphite sheet is attached to one side of the electrically insulating ceramic substrate using a thermally conductive adhesive material or a thermally conductive double-sided tape.
[0004] (Prior art literature)
[0005] Patent Document 1: Japanese Patent Publication No. 2003-174204 Summary of the invention
[0006] (Problem to be solved by the invention)
[0007] However, in the above-mentioned prior art, the adhesive may become a bottleneck of the properties of the substrate-graphite sheet composite. Specifically, the adhesive may become a thermal barrier or the heat resistance of the adhesive may limit the heat resistance of the composite. This problem is a new problem discovered by the inventors.
[0008] For example, when ceramics are used as a substrate, the following problems may occur. Ceramics have a high heat resistance temperature and can be used in high temperature environments. However, after bonding the graphite sheet to the ceramic using an adhesive, the resulting bond needs to be sintered at a temperature above 900°C, and the adhesive cannot withstand such a high temperature. In addition, even if a brazing material is used to bond the graphite sheet to the ceramic, the brazing material may migrate at high temperatures.
[0009] Therefore, there is a need for a graphite sheet that can be composited with a substrate without using a binder.
[0010] One aspect of the present invention aims to realize a graphite sheet that can be composited with a substrate without using an adhesive.
[0011] (Technical means to solve the problem)
[0012] A surface porous graphite sheet according to one aspect of the present invention comprises:
[0013] A porous layer located on one or both surfaces of the surface porous graphite sheet, and a graphite layer adjacent to the porous layer,
[0014] The pores of the porous layer include pores having pore diameters X and Y, wherein the pore diameter Y is larger than the pore diameter X, wherein the pore diameter X corresponds to the surface of the porous layer, and the pore diameter Y corresponds to the interior of the porous layer,
[0015] In a cross section obtained by vertically cutting the surface porous graphite sheet, the porosity of the following region A is greater than the porosity of the following region B.
[0016] Region A: a region extending from the surface of the surface porous graphite sheet on the side where the porous layer exists to a portion corresponding to 20% of the thickness of the surface porous graphite sheet;
[0017] Region B: the remaining region of the surface porous graphite sheet except region A.
[0018] In addition, a method for producing a surface porous graphite sheet according to one aspect of the present invention comprises:
[0019] providing a step of providing a laminated resin sheet in which a resin layer containing a pore former is laminated on one side or both sides of a resin sheet, wherein the resin layer containing a pore former contains a pore former that volatilizes under heating; and
[0020] The graphitization step is to graphitize the laminated resin sheet by heat-treating it at a temperature equal to or higher than the volatilization temperature of the pore-forming agent.
[0021] (Effects of the Invention)
[0022] According to one aspect of the present invention, a graphite sheet that can be composited with a substrate without using a binder can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of a surface porous graphite sheet according to one embodiment of the present invention.
[0024] Figure 2 This is a schematic diagram of a surface porous graphite sheet according to one embodiment of the present invention, showing regions A and B as viewed from a cross section of the surface porous graphite sheet.
[0025] Figure 3 This is a schematic diagram of a surface porous graphite sheet according to another embodiment of the present invention, showing regions A and B as viewed from a cross section of a surface porous graphite sheet having porous layers on both surfaces.
[0026] Figure 4 It is a schematic diagram of a cross section of a composite material according to one embodiment of the present invention.
[0027] Figure 5This is a schematic diagram of a method for producing a surface-layer porous graphite sheet according to one embodiment of the present invention.
[0028] Figure 6 This is a schematic diagram of a graphite sheet having a porous layer on its surface, which is produced by a method different from the production method of one embodiment of the present invention. DETAILED DESCRIPTION
[0029] The following describes the embodiments of the present invention in detail. However, the present invention is not limited to the following embodiments, and various changes can be made within the scope of the specification. The embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0030] In this specification, "A to B" indicating a numerical range means "A or more and B or less" unless otherwise specified.
[0031] 〔1. Surface porous graphite sheet〕
[0032] [1-1. Structure of the surface porous graphite sheet]
[0033] Below, reference Figures 1 to 4 , the structure of the surface porous graphite sheet according to one aspect of the present invention is described.
[0034] The surface porous graphite sheet 100 includes: a porous layer 20 and a graphite layer 10 adjacent to the porous layer 20. The porous layer 20 is a portion mainly composed of porous graphite. When the surface porous graphite sheet 100 is composited, the porous layer 20 imparts adhesion to the substrate 200 (especially a ceramic substrate). The graphite layer 10 is a portion mainly composed of less porous graphite having a smaller number of pores than the porous layer 20. It has high thermal conductivity and has a heat dissipation effect. Figure 1 The porous layer 20 is disposed on one surface layer of the surface porous graphite sheet 100, but the porous layer 20 may be disposed on both surface layers (see Figure 3 The surface porous graphite sheet 100').
[0035] There are a large number of pores 22 in the porous layer 20. Some of the pores 22 (pores 22a) have openings on the surface of the surface porous graphite sheet 100. Another part of the pores 22 (pores 22b) are buried inside the porous layer 20. The pores 22 also include pores 22a' having pore diameters X and Y, and the pore diameter Y is larger than the pore diameter X, wherein the pore diameter X corresponds to the surface of the porous layer 20, and the pore diameter Y corresponds to the inside of the porous layer 20 (see Figure 1 ). For example, the relationship between the pore sizes X and Y can be determined by referring to a cross-sectional photograph of the surface porous graphite sheet 100 .
[0036] When the surface porous graphite sheet 100 and the substrate 200 are composited, the substrate 200 will enter the pores 22a' whose pore size Y is larger than the pore size X. Therefore, the pores 22a' whose pore size Y is larger than the pore size X can give the surface porous graphite sheet 100 an anchoring effect relative to the substrate 200, thereby improving the adhesion between the surface porous graphite sheet 100 and the substrate 200 (see Figure 4 ).
[0037] Conventionally, it is difficult to directly compound graphite sheets with metal, ceramic and other substrates, and therefore adhesives are generally required for compounding. In contrast, the surface porous graphite sheet 100 has pores 22a' whose pore size Y is larger than pore size X, and therefore can be directly compounded with the substrate without the use of adhesives.
[0038] Thus, due to the presence of the pores 22a' whose pore size Y is larger than the pore size X, the adhesion between the surface porous graphite sheet 100 and the substrate 200 is achieved. Therefore, the condition that "the pores 22 of the porous layer 20 include pores 22a' having pore sizes X and pore size Y, and pore size Y is larger than pore size X, wherein the pore size X corresponds to the surface of the porous layer 20, and the pore size Y corresponds to the inside of the porous layer 20" can also be replaced by "adhesion between the surface porous graphite sheet 100 and the substrate 200". Specifically, from the results of the adhesion test performed according to the following steps 1 to 4, if there is no peeling of the entire surface of the graphite sheet at the interface between the graphite sheet and the ceramic, it can be said that "the pores 22 of the porous layer 20 include pores 22a' having pore sizes X and pore size Y, and pore size Y is larger than pore size X, wherein the pore size X corresponds to the surface of the porous layer 20, and the pore size Y corresponds to the inside of the porous layer 20" (for more specific test methods, see the examples described later).
[0039] 1. A ceramic material before sintering or an alumina-based ceramic adhesive is sandwiched between two surface-layer porous graphite sheets 100. At this time, the porous layer 20 is in contact with the ceramic material before sintering.
[0040] 2. Heat-treating the laminate obtained in step 1 to obtain a composite material.
[0041] 3. Clamp the ends of the two surface porous graphite sheets with a clamp, fold one surface porous graphite sheet at an angle of 180°, and peel off the surface porous graphite sheet 100 at a speed of 10 mm / sec.
[0042] 4. Check whether delamination occurs at the interface between the surface porous graphite sheet 100 and the ceramic, and / or whether interlayer delamination occurs inside the surface porous graphite sheet 100 .
[0043] In the surface porous graphite sheet 100, the porous layer 20 is concentrated in the surface layer. That is, the graphite sheet is not entirely porous. This can be described by the condition that "in the cross section obtained by vertically cutting the surface porous graphite sheet 100, the porosity of region A is greater than the porosity of region B" (see Figure 2 , 3 ).
[0044] Region A: A region extending from the surface of the surface porous graphite sheet 100 , 100 ′ on the side where the porous layer 20 is present to a portion corresponding to 20% of the thickness of the surface porous graphite sheet 100 .
[0045] Region B: the remaining region of the surface porous graphite sheet 100 excluding the region A.
[0046] Figure 2 The surface porous graphite sheet 100 shown in the figure has a porous layer 20 provided only on one surface layer. In such a surface porous graphite sheet 100, regions A and B are respectively Figure 2 On the other hand, Figure 3 The surface porous graphite sheet 100' shown in the figure has porous layers 20 on both of its surface layers. In such a surface porous graphite sheet 100', regions A and B are respectively Figure 3 The area shown.
[0047] “The surface of the surface porous graphite sheet 100 on the side where the porous layer 20 is present” refers to the surface on the side where the pores 22 a ′ having a pore size Y larger than the pore size X are present.
[0048] from Figure 2 , 3 Obviously, the boundary between region A and region B does not necessarily coincide with the boundary between the graphite layer 10 and the porous layer 20. The boundary between region A and region B may be located in the graphite layer 10 or in the porous layer 20. However, it is obvious that region A includes more porous layers 20 and region B includes more graphite layers 10. Therefore, in the cross section obtained by vertically cutting the surface porous graphite sheet 100, the porosity of region A is greater than that of region B.
[0049] The void ratio in the cross section can be calculated, for example, by taking a microscopic photograph of the cross section and using known image processing software.
[0050] In addition, “a cross section obtained by vertically cutting the surface porous graphite sheet 100” may also be “a cross section obtained by cutting the surface porous graphite sheet 100 in a manner vertically facing each graphite layer formed in the surface porous graphite sheet 100”. Of course, from the structure of a general graphite sheet, these two cross sections are usually basically the same.
[0051] [1-2. Characteristics of surface porous graphite sheets]
[0052] The lower limit of the thickness of the porous layer 20 is preferably 1 μm, more preferably 3 μm, and further preferably 5 μm. If the thickness of the porous layer is 1 μm or more, the probability that the thickness of the resin layer 40 containing the pore-forming agent exceeds the particle size of the pore-forming agent 42 used in the manufacturing method described later is high. Therefore, it is easy to form pores 22a' whose pore size Y is larger than the pore size X.
[0053] The upper limit of the thickness of the porous layer 20 is preferably 30 μm, more preferably 20 μm, and further preferably 10 μm. The thermal conductivity of the porous layer 20 is lower than that of the graphite layer 10, so if the thickness of the porous layer 20 is 30 μm or less, the entire surface porous graphite sheet 100 tends to have sufficient thermal conductivity.
[0054] The lower limit of the thickness of the surface porous graphite sheet 100 is preferably 20 μm, and more preferably 30 μm. The upper limit of the thickness of the surface porous graphite sheet 100 is preferably 100 μm, and more preferably 75 μm. When the thickness of the surface porous graphite sheet 100 is within the above range, even if a porous layer is provided, the effect of improving the heat dissipation of the substrate can be expected. In addition, when the thickness of the surface porous graphite sheet 100 is within the above range, the surface porous graphite sheet 100 has flexibility, and therefore has excellent handleability.
[0055] The thermal conductivity of the surface porous graphite sheet 100 in the film surface direction is preferably 800 W / mK or more, more preferably 1000 W / mK or more, further preferably 1200 W / mK or more, and further preferably 1400 W / mK or more. The upper limit of the thermal conductivity of the surface porous graphite sheet 100 in the film surface direction is not particularly limited, but can be 2000 W / mK.
[0056] When the thermal conductivity in the film surface direction is within the above range, the surface porous graphite sheet 100 can be preferably used as a heat dissipation member. As an example of a method for measuring the thermal conductivity in the film surface direction, there can be cited a measuring method described in the examples described later.
[0057] The tensile strength of the surface porous graphite sheet 100 is preferably 10 MPa or more, and more preferably 20 MPa or more. The upper limit of the tensile strength of the surface porous graphite sheet 100 is not particularly limited, but may be 200 MPa.
[0058] If the tensile strength is within the above range, it can be said that the surface porous graphite sheet 100 has sufficient strength as a material. An example of a method for measuring the tensile strength is a method specified in ASTM-D-882.
[0059] 〔2. Composite materials and electronic components〕
[0060] One aspect of the present invention is a composite material 500 formed by laminating a surface porous graphite sheet 100 and a substrate 200. The substrate 200 may be an inorganic material or an organic material. For example, if the composite material is used as a cooling component material for an electronic component or electronic material, the substrate 200 is preferably an inorganic material. Examples of inorganic materials include metals and ceramics.
[0061] A known metal material can be used appropriately as the substrate 200. Specific examples of the metal material include gold, silver, copper, nickel, aluminum, molybdenum, tungsten, and alloys containing these.
[0062] A known ceramic material can be used appropriately as the substrate 200. Specific examples of the ceramic material include aluminum oxide, zirconium, silicon carbide, silicon nitride, boron nitride, and aluminum nitride.
[0063] The thickness of the composite material 500 is preferably 25 μm or more, more preferably 50 μm or more. In addition, the thickness of the composite material 500 is preferably 50 mm or less, more preferably 10 mm or less. When the thickness of the composite material 500 is within the above range, sufficient strength and heat dissipation can be obtained.
[0064] One aspect of the present invention is an electronic component or an electronic material cooling component including a composite material 500. Specific examples of the electronic component include a glass epoxy resin substrate, a fluororesin substrate, a metal substrate, a ceramic substrate, etc. Specific examples of the electronic material cooling component include a heat spreader, a heat sink, a heat pipe, a heat fin, etc.
[0065] [3. Method for producing surface porous graphite sheet]
[0066] [3-1. Provision process]
[0067] Below, reference Figure 5 , a method for producing a surface porous graphite sheet according to one aspect of the present invention is described.
[0068] The manufacturing method includes a step of providing a laminated resin sheet 50 ( Figure 5 The laminated resin sheet 50 is a sheet in which a porogen-containing resin layer 40 is laminated on one side or both sides of a resin sheet 30. The porogen-containing resin layer 40 contains a porogen 42 that volatilizes under heating.
[0069] Sometimes, the resin sheet 30 also contains substances that volatilize under heating (calcium phosphate, calcium hydrogen phosphate, calcium carbonate, silicon dioxide, etc.). These substances are used to expand the interlayer space of each graphite layer formed in the graphite layer 10. However, compared with the content rate of the substances that volatilize under heating contained in the resin sheet 30, the content rate of the pore-forming agent 42 contained in the resin layer 40 containing the pore-forming agent is very large.
[0070] The content of the pore former 42 in the pore former-containing resin layer 40 is preferably 7% by weight or more, more preferably 10% by weight or more, further preferably 15% by weight or more, further preferably 20% by weight or more, further preferably 25% by weight or more, further preferably 30% by weight or more. The content of the pore former 42 can be obtained by the formula "content of the pore former 42 = weight of the pore former 42 / weight of the resin solid component in the pore former-containing resin layer 40 (excluding the weight of the pore former 42) × 100". That is, as described later, if the pore former-containing resin layer 40 is formed by applying a varnish, the weight of the solvent contained in the varnish does not affect the content of the pore former 42 in the pore former-containing resin layer 40.
[0071] The upper limit of the content of the porogen 42 in the porogen-containing resin layer 40 is preferably 75% by weight, more preferably 60% by weight, and further preferably 50% by weight.
[0072] On the other hand, the content of the substance volatilizing under heating in the resin sheet 30 is preferably 1 wt% or less, more preferably 0.5 wt% or less, and further preferably 0.2 wt% or less. The content can be obtained by the formula "content of substance volatilizing under heating = weight of substance volatilizing under heating / weight of resin solid content in the resin sheet 30 (excluding the weight of substance volatilizing under heating) × 100".
[0073] When comparing the "content of the pore-forming agent 42 in the pore-forming agent-containing resin layer 40" and the "content of substances volatilizing under heating in the resin sheet 30" thus obtained, the former is preferably 10 times or more of the latter, more preferably 50 times or more, and even more preferably 100 times or more.
[0074] [3-2. Graphitization process]
[0075] The manufacturing method according to one aspect of the present invention further includes a graphitization step of graphitizing the laminated resin sheet 50 by heat treatment. The temperature of the heat treatment is equal to or higher than the volatilization temperature of the pore former 42 .
[0076] In the graphitization step, the laminated resin sheet 50 is heat-treated at a temperature higher than the volatilization temperature of the pore-forming agent 42. Therefore, in the graphitization step, the pore-forming agent 42 contained in the pore-forming agent-containing resin layer 40 is volatilized. Then, the heat treatment is performed until the laminated resin sheet 50 is completely graphitized, so that a surface porous graphite sheet 100 having a porous layer 20 on one or both surface layers can be finally obtained.
[0077] Among them, Figure 5As shown in the upper column of FIG. 4 , at least a portion of the porogen 42 is embedded and distributed inside the porogen-containing resin layer 40. Therefore, the pores 22 formed by the volatilization of the porogen 42 will include pores 22a' whose pore diameter X is smaller than the pore diameter Y.
[0078] In contrast, in a graphite sheet obtained by providing holes in the surface layer by conventional techniques (laser irradiation, etc.), holes 22a' whose hole diameter X is smaller than the hole diameter Y cannot be obtained. Figure 6 A graphite sheet 1000 having holes on its surface is shown, which is manufactured by a typical conventional technique. The graphite sheet 1000 has holes 810 (i) whose diameter increases as it approaches the surface, or (ii) whose diameter is almost constant when viewing the entire pores.
[0079] In addition, in the manufacturing method of one embodiment of the present invention, the laminated resin sheet 50 is graphitized. That is, the graphitization is performed in the state where the resin sheet 30 and the resin layer 40 containing the pore-forming agent are laminated. Therefore, in the completed graphite sheet, the porous layer 20 is concentrated on the surface layer. On the contrary, if the resin sheet before the graphitization step contains the pore-forming agent uniformly, the completed graphite sheet should be porous as a whole.
[0080] In the graphitization step, the laminated resin sheet 50 is heat treated at 700°C to 1400°C to be carbonized, and then heat treated at 2000°C to 3500°C to be graphitized. The volatilization temperature of the pore former 42 is not particularly limited as long as it is in the aforementioned temperature range, but it is preferred that the pore former 42 volatilizes in the graphitization stage rather than in the carbonization stage. That is, the volatilization temperature of the pore former 42 is preferably 1400°C to 3500°C, and more preferably 2000°C to 3000°C.
[0081] [3-3. Method for producing laminated resin sheet]
[0082] The laminated resin sheet 50 can be produced by laminating the resin layer 40 containing the pore-forming agent on one side or both sides of the resin sheet 30. As one example, the laminated resin sheet 50 can be produced by a wet method of applying a resin varnish containing the pore-forming agent 42 on one side or both sides of the resin sheet 30 and then drying it. As another example, a resin varnish layer containing the pore-forming agent 42 can be provided on one side or both sides of a resin sheet 30 precursor, and then the resin sheet 30 and the resin layer 40 containing the pore-forming agent can be produced simultaneously.
[0083] When the laminated resin sheet 50 is produced by the wet method, there is no particular limitation on the method for coating the resin varnish on the resin sheet 30. As the coating method, a known method such as gravure coating, dip coating, bar coating, and die coating can be used.
[0084] The thickness of the resin sheet 30, the resin layer 40 containing a pore former, and the laminated resin sheet 50 can be appropriately set according to the desired thickness of the graphite layer 10, the porous layer 20, and the surface porous graphite sheet 100. As an example, the thickness of the resin sheet 30 is preferably 25 to 180 μm, and more preferably 50 to 130 μm. The thickness (thickness in a dry state) of the resin layer 40 containing a pore former is preferably 1 to 60 μm, and more preferably 5 to 20 μm. The thickness (thickness in a dry state) of the laminated resin sheet 50 is preferably 40 to 200 μm, and more preferably 60 to 150 μm.
[0085] (resin sheet)
[0086] The material of the resin sheet 30 is not particularly limited as long as it can be graphitized by heat treatment. In one example, the material of the resin sheet 30 is a polyimide sheet. In another example, the material of the resin sheet 30 is a carbonized sheet obtained by carbonizing a polyimide sheet at a high temperature (e.g., above 800° C.).
[0087] The polyimide sheet may be, for example, a polyimide sheet obtained using an acid dianhydride component and a diamine component as raw materials.
[0088] Specific examples of the acid dianhydride component include pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 1,1-(3,4-dicarboxyphenyl)ethanedicarboxylic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, oxybis(phthalic acid) dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), and derivatives thereof.
[0089] Specific examples of the diamine component include 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminodiphenylmethane, biphenyl diamine, 3,3'-dichlorobiphenyl diamine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,5-diaminonaphthalene, 4,4'-diaminodiphenyl diethylsilane, 4,4'-diaminodiphenyl silane, 4,4'-diaminodiphenyl ethyl phosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-aniline, 1,3-diaminobenzene, 1,2-diaminobenzene, and analogs thereof.
[0090] The above components may be used alone or in combination of two or more.
[0091] (Pore Forming Agent)
[0092] The material of the pore former 42 is not particularly limited as long as it is a substance that forms pores by volatilization through heat treatment. In one embodiment, the pore former 42 is one or more selected from metal oxides, metal salts, metal nitrides, metal carbides, and metal powders.
[0093] Specific examples of metal oxides include magnesium oxide, aluminum oxide, calcium oxide, titanium oxide, zirconium oxide, hafnium oxide, gallium oxide, cerium oxide, nickel oxide, chromium oxide, and yttrium oxide. Examples of metal salts include magnesium carbonate, calcium carbonate, calcium phosphate, and sodium phosphate. Examples of metal nitrides include titanium nitride, zirconium nitride, niobium nitride, tantalum nitride, and chromium nitride. Examples of metal carbides include tungsten carbide, molybdenum carbide, titanium carbide, tantalum carbide, and niobium carbide. Examples of metal powders include magnesium powder, molybdenum powder, tantalum powder, tungsten powder, nickel powder, zirconium powder, hafnium powder, and titanium powder.
[0094] Among the substances exemplified above, one or more selected from magnesium oxide, magnesium carbonate and aluminum oxide is preferred. These substances have the advantages of being cheaply available, being able to stably exist in the air, having a high melting point and being less dangerous. In addition, from the viewpoint of obtaining a porous layer 20 with good adhesion to the substrate 200, the pore-forming agent 42 is preferably one or more selected from magnesium oxide and magnesium carbonate.
[0095] The particle size of the pore former 42 is preferably 0.1 to 20 μm, more preferably 1 to 10 μm, in terms of the volume-based average particle size (D50). The particle size of the pore former 42 within the above range has the advantage of being able to form pores of a size suitable for bonding to the substrate. The volume-based average particle size can be measured using a general particle size meter.
[0096] (Pore-Forming Agent-Containing Resin Layer)
[0097] The resin layer 40 containing a pore former is not particularly limited as long as it is a resin layer in which the pore former 42 is distributed and carbon remains after heat treatment. In one embodiment, a varnish containing polyamic acid and a pore former is applied to the resin sheet 30 to form the resin layer 40 containing a pore former (wherein the polyamic acid is a substance that becomes polyimide by heat treatment and is graphitized by further heat treatment).
[0098] 〔Summarize〕
[0099] The present invention includes the following aspects.
[0100] <1>
[0101] A surface porous graphite sheet 100 (100') comprising:
[0102] The porous layer 20 located on one or both surfaces of the surface porous graphite sheet 100 (100'), and the graphite layer 10 adjacent to the porous layer 20,
[0103] The pores 22 of the porous layer 20 include pores 22a' having pore diameters X and Y, wherein the pore diameter Y is larger than the pore diameter X, wherein the pore diameter X corresponds to the surface of the porous layer 20, and the pore diameter Y corresponds to the interior of the porous layer 20.
[0104] In a cross section obtained by vertically cutting the surface porous graphite sheet 100 (100'), the porosity of the following region A is greater than the porosity of the following region B,
[0105] Region A: a region extending from the surface of the surface porous graphite sheet 100 (100') on the side where the porous layer 20 is present to a position corresponding to 20% of the thickness of the surface porous graphite sheet 100 (100');
[0106] Region B: the remaining region of the surface porous graphite sheet 100 (100') except the region A.
[0107] <2>
[0108] The surface porous graphite sheet 100 ( 100 ′) according to <1>, wherein the thermal conductivity of the surface porous graphite sheet 100 ( 100 ′) in the film surface direction is 800 W / mK or more.
[0109] <3>
[0110] A composite material 500 is formed by laminating the surface porous graphite sheet 100 (100') and the substrate 200 as described in <1> or <2>.
[0111] <4>
[0112] An electronic component comprises the composite material 500 described in <3>.
[0113] <5>
[0114] A method for manufacturing a surface porous graphite sheet 100 (100'), comprising:
[0115] providing a step of providing a laminated resin sheet 50 formed by laminating a porogen-containing resin layer 40 on one side or both sides of a resin sheet 30, wherein the porogen-containing resin layer 40 contains a porogen 42 that volatilizes under heating; and
[0116] In the graphitization step, the laminated resin sheet 50 is graphitized by heat treatment at a temperature equal to or higher than the volatilization temperature of the pore former 42 .
[0117] <6>
[0118] The manufacturing method according to <5>, wherein the pore former 42 is one or more selected from the group consisting of metal oxides, metal salts, metal nitrides, metal carbides, and metal powders.
[0119] <7>
[0120] The method for producing a surface porous graphite sheet according to <5> or <6>, wherein the pore former 42 is at least one selected from magnesium oxide, magnesium carbonate, and aluminum oxide.
[0121] (Example)
[0122] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment.
[0123] [Evaluation method of graphite sheet properties]
[0124] [Adhesion to ceramics]
[0125] Two graphite sheets obtained from the examples or comparative examples are prepared. Ceramic adhesive (manufactured by ThreeBond Co., Ltd., heat-resistant inorganic adhesive 3732, alumina system) is applied to one surface of one of the graphite sheets, and then sandwiched with another graphite sheet. At this time, the surface of the graphite sheet adjacent to the ceramic adhesive is the surface on the side where the porous layer is formed. Next, the graphite sheet sandwiched with the ceramic adhesive is heated to 1000°C at a heating rate of 5°C / min under a nitrogen atmosphere. Then, heat treatment is performed at 1000°C for 10 minutes to dry the composite material. After the obtained composite material is cooled to room temperature, the ends of the two surface porous graphite sheets are clamped with a clamp, and the surface porous graphite sheet on one side is folded back to an angle of 180°, and the surface porous graphite sheet on the other side is peeled off at a speed of 10 mm / sec, and the adhesion is evaluated. The evaluation is as follows in order of the excellent adhesion with ceramics.
[0126] ⊚: The graphite sheet was not peeled off at the interface with the ceramic, and only interlayer peeling occurred inside the graphite sheet (the graphite sheet was not peeled off at all).
[0127] ○: A portion of the graphite sheet peeled off at the interface with the ceramic, but interlayer peeling occurred inside the graphite sheet in more than half of the area (most of the graphite sheet was not peeled off).
[0128] △: The graphite sheet peeled off at the interface with the ceramic over more than half of the area, but interlayer peeling also partially occurred inside the graphite sheet (part of the graphite sheet was not peeled off).
[0129] ×: The entire surface of the graphite sheet peeled off at the interface with the ceramic (the graphite sheet was completely peeled off).
[0130] [Heat dissipation]
[0131] (Thermal diffusivity)
[0132] The thermal diffusivity of the graphite sheets obtained in the examples or comparative examples was measured using a thermal diffusivity measuring device based on the optical alternating current method ("LaserPit" manufactured by ULVAC RIKEN CO., LTD.). As a sample, a graphite sheet cut into a size of 4 mm × 40 mm was used. The measurement conditions were an alternating current of 10 Hz in an atmosphere of 20°C.
[0133] (Density of graphite sheet)
[0134] The weight of a 3 cm square graphite sheet (g) is divided by the volume (cm) calculated by multiplying the length, width, and thickness of the film. 3 ), and thus calculate the density of the graphite sheet.
[0135] (Evaluation of heat dissipation)
[0136] The thermal conductivity in the film surface direction was calculated according to the formula "thermal diffusivity × density × specific heat = thermal conductivity in the film surface direction". The heat dissipation was evaluated based on the obtained thermal conductivity value. The evaluation criteria were as follows in order of the heat dissipation.
[0137] ◎: 1200W / mK or more.
[0138] ○: 1000W / mK or more.
[0139] △: 800W / mK or more.
[0140] ×: Less than 800W / mK.
[0141] [Example 1]
[0142] [Preparation of polyamic acid varnish (1)]
[0143] In a dimethylformamide solution in which 4,4'-diaminodiphenyl ether (ODA) is dissolved, pyromellitic anhydride (PMDA) in an equimolar amount to ODA is further dissolved to obtain a polyamic acid solution containing 18.5% by weight of polyamic acid. Magnesium oxide is added as a pore-forming agent to the obtained polyamic acid solution to obtain a polyamic acid varnish (1). The amount of magnesium oxide added is such that the magnesium oxide concentration relative to the solid content in the polyamic acid reaches 30% by weight.
[0144] [Preparation of laminated polyimide film (1)]
[0145] A polyamic acid varnish (1) was applied to one side of a polyimide sheet (Apical AH manufactured by KANEKA Co., Ltd., thickness: 75 μm). The amount of coating was set so that the thickness after drying would be 10 μm. Next, the obtained coating was heated in a hot air oven to dry it. During the heating process, the temperature was increased in stages as follows: (i) heating at 100°C for 4 minutes, (ii) heating to 200°C to 300°C over 20 minutes, and (iii) heating at 400°C for 5 minutes. Thus, a laminated polyimide film (1) (thickness: 85 μm) was produced.
[0146] [Manufacturing of graphite sheet (1)]
[0147] The laminated polyimide film (1) (length × width × thickness: 50 mm × 50 mm × 85 μm) was sandwiched between graphite sheets (length × width: 70 mm × 70 mm). At this time, the laminated polyimide film (1) and the graphite sheets were laminated alternately. The laminated body was heated to 1000°C at a heating rate of 0.5°C / min in a nitrogen atmosphere, and then heat-treated at 1000°C for 10 minutes to carbonize it.
[0148] Then, the heat treatment temperature was raised to 2800°C (i.e., the maximum graphitization temperature) at a heating rate of 1.0°C / min, and maintained at 2800°C for 10 minutes, thereby obtaining a graphite sheet (1). In the temperature range of room temperature to 2200°C, the heat treatment environment was under reduced pressure, and in the temperature range exceeding 2200°C, the heat treatment environment was under an argon atmosphere. The graphitized laminated polyimide film (1) was taken out from between the graphite sheets, and each of the graphitized products was sandwiched with a PET film (length × width × thickness: 200mm × 200mm × 400μm), and compressed using a compression molding machine. The pressure applied at this time was 10MPa.
[0149] [Example 2]
[0150] In the preparation procedure of polyamic acid varnish (1), the concentration of magnesium oxide relative to the solid content in polyamic acid was changed to 10 wt % to obtain polyamic acid varnish (2), and a graphite sheet (2) was produced in the same manner as in Example 1 except that polyamic acid varnish (2) was used.
[0151] [Example 3]
[0152] In the preparation step of the polyamic acid varnish (1), the concentration of magnesium oxide relative to the solid content in the polyamic acid was changed to 60 wt % to obtain a polyamic acid varnish (3), and a graphite sheet (3) was produced in the same manner as in Example 1 except that the polyamic acid varnish (3) was used.
[0153] [Example 4]
[0154] In the preparation step of the polyamic acid varnish (1), the pore former was changed to magnesium carbonate to obtain a polyamic acid varnish (4), and a graphite sheet (4) was prepared in the same manner as in Example 1 except that the polyamic acid varnish (4) was used.
[0155] [Example 5]
[0156] A graphite sheet (5) was prepared in the same manner as in Example 1 except that the pore former was changed to alumina in the preparation step of the polyamic acid varnish (1) to obtain the polyamic acid varnish (5). The polyamic acid varnish (5) was used.
[0157] [Example 6]
[0158] In the preparation step of the laminated polyimide film (1), polyamic acid varnish (1) was applied on both sides of Apical AH (thickness: 75 μm) manufactured by KANEKA Co., Ltd., and the coating amount on each side was set so that the thickness of each side after drying was 10 μm. Except for this, a graphite sheet (6) was prepared by the same method as in Example 1.
[0159] [Comparative Example 1]
[0160] A graphite sheet (1a) was prepared in the same manner as in Example 1 except that no pore-forming agent was added in the step of preparing the polyamic acid varnish (1) to obtain the polyamic acid varnish (1a), and the polyamic acid varnish (1a) was used.
[0161] [Comparative Example 2]
[0162] The graphite sheet (1a) was irradiated with laser light to form holes in the surface layer, thereby obtaining a graphite sheet (2a). The density of the holes was about 25 / cm 2 , the pore diameter is about 50μm, and the pore depth is about 5μm.
[0163] [Comparative Example 3]
[0164] While cooling the polyamic acid varnish (1), acetic anhydride in an amount of 1 equivalent to the carboxyl group in the polyamic acid, isoquinoline in an amount of 1 equivalent to the carboxyl group in the polyamic acid, and an imidization catalyst containing dimethylformamide were added, and degassed. Next, the mixed solution was applied to an aluminum foil in a manner to have a thickness of 75 μm after drying to obtain a mixed solution layer. The mixed solution layer on the aluminum foil was dried using a hot air oven and a far-infrared heater.
[0165] The drying method is as follows. First, the mixed solution layer on the aluminum foil is dried in a hot air oven at 120°C for 360 seconds to form a self-supporting gel film. The gel film is peeled off from the aluminum foil and fixed to a frame. The gel film is then heated and dried in stages as follows: heated in a hot air oven at 120°C for 45 seconds, heated at 275°C for 60 seconds, heated at 400°C for 60 seconds, heated at 450°C for 70 seconds, and heated at 460°C for 30 seconds using a far-infrared heater. In this way, a polyimide film (A) with a thickness of 75 μm is produced.
[0166] This polyimide film (A) was heated in the same manner as in Example 1 to obtain a graphite sheet (3a).
[0167] [Comparative Example 4]
[0168] In the step of producing the laminated polyimide film (1), after polyamic acid varnish (1a) is applied on one side of a polyimide sheet, magnesium oxide powder is sprinkled on the surface. That is, polyamic acid varnish not containing a pore-forming agent is applied on the surface of the polyimide film, and then the pore-forming agent is sprinkled from above the polyamic acid varnish. Using the obtained coating, a graphite sheet (4a) is obtained in the same manner as in Example 1.
[0169] 〔result〕
[0170] The evaluation results of the graphite sheets (1) to (6) and (1a) to (4a) are shown in Table 1 below.
[0171] (Table 1)
[0172] Table 1
[0173]
[0174] In Examples 1 to 6, a resin layer containing a pore former (polyamic acid varnish containing a pore former) is laminated on one side or both sides of a resin sheet (polyimide sheet) to form a laminated resin sheet, and the laminated resin sheet is heat treated to obtain a graphite sheet. As a result, the obtained graphite sheets (1) to (6) are surface porous graphite sheets having a porous layer on one side or both sides. The porous layer of the graphite sheets (1) to (6) contains pores whose pore size Y corresponding to the inside of the porous layer is larger than the pore size X corresponding to the surface of the porous layer. Therefore, the adhesion between the graphite sheets (1) to (6) and the ceramic is above a certain level.
[0175] On the other hand, the graphite sheet (1a) has a non-porous surface layer. Therefore, the graphite sheet (1a) has no adhesiveness to the ceramic, and complete peeling occurs at the interface.
[0176] In the manufacturing methods of Comparative Examples 2 and 4, the pores contained in the porous layer are all pores whose pore diameter X corresponding to the surface of the graphite sheet and the pore diameter Y corresponding to the inside of the porous layer are substantially the same. Therefore, the graphite sheets (2a) and (4a) have no adhesion to the ceramic, and complete peeling occurs at the interface.
[0177] In the graphite sheet (3a) prepared in Comparative Example 3, the resin sheet as a material contains a pore-forming agent throughout the entire sheet and is therefore porous as a whole. Therefore, the thermal conductivity of the graphite sheet in the film surface direction is low and the heat dissipation is poor.
[0178] (Industrial Applicability)
[0179] The present invention can be used, for example, in the manufacture of a composite material, which can be used, for example, in heat dissipation components such as multilayer ceramic substrates.
[0180] <Description of Reference Numerals>
[0181] 10 Graphite layer
[0182] 20 Porous layer
[0183] 22 holes
[0184] 30 Resin Sheet
[0185] 40 Resin layer containing pore forming agent
[0186] 42 pore former
[0187] 50 Laminated resin sheet
[0188] 100 Surface porous graphite sheet
[0189] 100' Surface porous graphite sheet
[0190] 500 Composite Materials
Claims
1. A surface porous graphite sheet, comprising: A porous layer located on one or both surfaces of the surface porous graphite sheet, and a graphite layer adjacent to the porous layer, The pores of the porous layer include pores with pore diameters X and Y, and the pore diameter Y is larger than the pore diameter X, wherein: The pore size X corresponds to the surface of the porous layer, and the pore size Y corresponds to the interior of the porous layer. In a cross section obtained by vertically cutting the surface porous graphite sheet, the porosity of the following region A is greater than the porosity of the following region B, Region A: a region extending from the surface of the surface porous graphite sheet on the side where the porous layer exists to a portion corresponding to 20% of the thickness of the surface porous graphite sheet; Region B: the remaining region of the surface porous graphite sheet except region A, The thermal conductivity of the surface porous graphite sheet in the film surface direction is above 800 W / mK.
2. A composite material, which is formed by laminating the surface porous graphite sheet according to claim 1 and a substrate.
3. An electronic component comprising the composite material according to claim 2.
4. The method for producing a surface porous graphite sheet according to claim 1, comprising: providing a step of providing a laminated resin sheet in which a resin layer containing a pore former is laminated on one side or both sides of a resin sheet, wherein the resin layer containing a pore former contains a pore former that volatilizes under heating; and a graphitization step of graphitizing the laminated resin sheet by heat treating the laminated resin sheet at a temperature higher than the volatilization temperature of the pore-forming agent, Wherein, the resin sheet is a polyimide sheet.
5. The manufacturing method according to claim 4, wherein: The pore-forming agent is one or more selected from metal oxides, metal salts, metal nitrides, metal carbides and metal powders.
6. The manufacturing method according to claim 4 or 5, wherein: The pore former is one or more selected from magnesium oxide, magnesium carbonate and aluminum oxide.
Citation Information
Patent Citations
Thermoelectric conversion device
JP2003174204A
Method for manufacturing a carbide ceramic contact body and carbide ceramic contact body
EP1876159A1